Assessment of electronic media use in children and adolescents with attention deficit hyperactivity disorder - Gormez, Vahdet; Orengul, ABDURRAHMAN CAHİD; ÖRENGÜL, ABDURRAHMAN CAHİD (My University, 2017)
Objective: Electronic media use is an emerging area of research interest, however its relationship with Attention Deficit hyperactivity disorder (ADHD) is neglected in Turkish literature. We therefore aimed to examine its relationship with certain variables and ADHD subtypes. Methods: A total of 360 participants aged between 6-18 years, who attended Bezmialem University, Child and Adolescent Psychiatry Outpatient Clinic between January 2016 and October 2016, were screened with the Schedule for Affective Disorders and Schizophrenia for School Age Children K-SADS) interview to ascertain diagnoses and a sociodemographic information tool was used to collect the relevant data. Results: The mean age of the sample was 9.47 +/- 2.67 years, and 81.9% of them consisted of males. 20.6% of the sample was reported to spend between 2 and 4 hours a day using electronic media gadgets (TV viewing, cell phone and/or tablet/computer use), while 4-6 hours of use was reported in 15.8%, 6-8 hours in 11.4%, 8-10 hours in 9.4% and more than 10 hours/day in 18.2% of the total sample. Heavy users of electronic media (> 6 hours/day) reportedly had significantly higher academic achievement and lower socioeconomic status as compared to those who used it at medium (2-6 hours/day) and low levels (< 2 hours/day). Gender, the content of TV viewing and total electronic media use within the household also significantly differed between the heavy, medium and low intensity users. Regression analyses revealed that total daily electronic media use for 10 hours and above was significantly and independently associated with the current family psychiatric illness and low academic achievement of the child. Conclusion: To the best of our knowledge, this is the first study reporting use of a variety of electronic media gadgets in a Turkish clinical sample of children and adolescents with ADHD. Results are in line with the existing international literature and highlights the excessive electronic media use in this clinical population. We recommend a routine screening for electronic media exposure in ADHD minors and increase awareness in their families and schools. Longitudinal and methodologically more robust studies are needed to examine cause-effect relationships.